Liquid membrane extraction of silver from photographic waste - Mat, Hanapi; Othman, Norasikin (Universiti Teknologi Malaysia, 2006)
Semiconductor waste can cause a serious problem in term of storage and pollution since it contains high concentration of heavy metals. One of the possible alternatives is to treat this waste by recovering the precious metals such as silver. In this study, an attempt was made to remove the silver selectively from selected semiconductor waste using leaching, precipitation and liquid-liquid extraction processes. From the characterization study, it was found that the semiconductor waste contains 5.92 % of silver which mostly existed in the form of Ag and AgCl compounds. Therefore, chloride leaching has been selected to leach silver from the waste by forming soluble silver chloro complexes. The extent of silver leaching increases with increasing the chloride concentration which could be achieved by either increasing the HCl concentration or addition of high NaCl concentration. The process involved could be explained using shrinking-core model which indicated that the leaching rate was controlled by outward diffusion of silver chloro complexes from the particle surface. These complexes are stable especially at pH 12. Thus, pH adjustment on leaching solution was successfully recovered silver selectively and removed copper and iron precipitate through centrifugation. In the liquid-liquid extraction studies, the extent of silver extraction using Cyanex 272 from leaching solution is low and independent of pH. This result might due to high stability of silver chloro complexes. Therefore, dithizone has been selected due to its soft donor atom of sulfur which is capable to bind with soft acid of silver by forming silver dithizonate. This extraction process as able to extract silver selectively up to almost 100 % and dependence of pH. As an overall, the proposed silver recovery procedure can remove more than 45 % of silver from the selected semiconductor waste.